The Influence of Professionalism and Motivation on Work Morale and Its Impact on the Performance of Personnel at the Jambi Regional Police Traffic Directorate - Sukarman, Sukarman; Suryani, Arna; Sudirman, Sudirman (Dinasti Publisher, 2026)
This study aims to analyze the influence of professionalism and work motivation on work morale and its impact on the performance of personnel at the Jambi Regional Police Traffic Directorate. The study used a quantitative approach with a descriptive and verification design. The study population included all 131 personnel at the Jambi Regional Police Traffic Directorate, all of whom served as respondents. Data collection was conducted through the distribution of questionnaires compiled based on research variable indicators and measured using a Likert scale. The data obtained were analyzed using path analysis techniques to test the direct and indirect effects between variables. The results showed that professionalism and work motivation simultaneously and partially had a positive and significant effect on personnel work morale. In addition, professionalism and work motivation also had a positive and significant effect on personnel performance. Work morale was proven to have a positive and significant effect on personnel performance and acted as an intervening variable that strengthened the influence of professionalism and work motivation on the performance of personnel at the Jambi Regional Police Traffic Directorate. These findings indicate that personnel performance is not only determined by ability and work drive alone, but is also greatly influenced by psychological conditions and work attitudes reflected in work morale. Based on the results of the study, it was concluded that efforts to improve the performance of personnel at the Jambi Regional Police Traffic Directorate need to be carried out comprehensively through strengthening professionalism, increasing work motivation, and fostering work morale on an ongoing basis to support the realization of optimal and professional traffic services.